Top Questions in the Diagnosis and Treatment of Pulmonary M. abscessus Disease. (14th May 2019) - Nathavitharana, Ruvandhi R; Strnad, Luke; Lederer, Philip A; Shah, Maunank; Hurtado, Rocio M
Abstract : Mycobacterium abscessus pulmonary disease is particularly challenging to treat, given its intrinsic drug resistance and limited data to guide management. In this paper, we discuss commonly encountered clinical management questions including diagnostic criteria, interpretation of drug susceptibility testing, approach to treatment, including choice of intravenous versus oral antibiotics, and adjunctive strategies, including airway clearance and surgery. Abstract: Mycobacterium abscessus disease is particularly challenging to treat, given the intrinsic drug resistance of this species and the limited data on which recommendations are based, resulting in a greater reliance on expert opinion. We address several commonly encountered questions and management considerations regarding pulmonary Mycobacterium abscessus disease, including the role of subspecies identification, diagnostic criteria for determining disease, interpretation of drug susceptibility test results, approach to therapy including the need for parenteral antibiotics and the role for new and repurposed drugs, and the use of adjunctive strategies such as airway clearance and surgical resection.